2002
DOI: 10.1080/02626660209492948
|View full text |Cite
|
Sign up to set email alerts
|

Use of regionalized stormflow coefficients with a view to hydroclimatological hazard mapping

Abstract: An attempt was made to compensate for the lack of long hydrological time series and the lack of information on maximum streamflow in the Alzette River basin (Luxembourg) via the regionalization of stormflow coefficients. Streamflow data recorded since 1995 with a very dense streamgauge network allowed the determination of maximum stormflow coefficients in 18 sub-basins of the Alzette. The stormflow coefficients were then regionalized via stepwise multiple regression analysis for 83 different sub-basins of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 9 publications
(10 reference statements)
2
38
0
Order By: Relevance
“…5 it is clear that, as the catchment becomes wet, the hydrological response increases and, consequently, it represents a greater percentage of rainfall. Probably the antecedent soil moisture state plays an important role in the hydrological response of the catchment, as has been often suggested for temperate humid catchments (Dunne et al 1975, Pfister et al 2002, Norbiato et al 2009, Penna et al 2011. However, over the study period, the observed seasonality of the runoff coefficients was also possibly affected by rainfall characteristics, such as large and long rainfall events occurring in 2006.…”
Section: Hydrological Response At the Event Scalementioning
confidence: 68%
See 1 more Smart Citation
“…5 it is clear that, as the catchment becomes wet, the hydrological response increases and, consequently, it represents a greater percentage of rainfall. Probably the antecedent soil moisture state plays an important role in the hydrological response of the catchment, as has been often suggested for temperate humid catchments (Dunne et al 1975, Pfister et al 2002, Norbiato et al 2009, Penna et al 2011. However, over the study period, the observed seasonality of the runoff coefficients was also possibly affected by rainfall characteristics, such as large and long rainfall events occurring in 2006.…”
Section: Hydrological Response At the Event Scalementioning
confidence: 68%
“…It affects infiltration capacity and the capability of soils to store new rainfall water. Hence, the different runoff generating processes are highly regulated by soil characteristics and especially by soil moisture, and not by rainfall characteristics (Jordan 1994, Pfister et al 2002, Merz and Blöschl 2009.…”
Section: Introductionmentioning
confidence: 99%
“…basins ranging in size from 10 km 2 to 10 3 km 2 ; Blöschl, 1996) to rainfall during winter. The permeability of the substratum was found to be an important basin characteristic in describing the C-value of basins in the Grand Duchy of Luxembourg (Pfister et al, 2002) and it will serve in this study as a single independent parameter in a first model, which is based on linear regression, to describe the C-value with. Since soils form the first medium between precipitation and runoff generating processes after the vegetation cover, they will serve in this study as independent parameters for a second model.…”
Section: Introductionmentioning
confidence: 99%
“…The previously named basin characteristics served as independent parameters. The C-value is defined as the ratio between storm flow and rainfall, is supposed to be basin specific and to have a strong seasonal variability, and should be more or less constant during winter, expressing the saturated state of the basin (Pfister et al, 2002). Uhlenbrook et al (2004) pointed out that in meso-scale basins processes combine into a more complex way, producing an integrated runoff response to rainfall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation